Jet Quenching in Relativistic Heavy Ion Collisions at the LHC - Angerami, Aaron; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This thesis presents the first measurements of jets in relativistic heavy ion collisions as reported by the ATLAS Collaboration. These include the first direct observation of jet quenching through the observation of a centrality-dependent dijet asymmetry. Also, a series of jet suppression measurements are presented, which provide quantitative constraints on theoretical models of jet quenching. These results follow a detailed introduction to heavy ion physics with emphasis on the phenomenon of jet quenching and a comprehensive description of the ATLAS detector and its capabilities with regard to performing these measurements.
Introduction -- Background -- Experimental Setup -- Jet Reconstruction -- Data Analysis -- Results -- Conclusion.
Keywords: Physics; Nuclear physics; Particle acceleration; Physics; Nuclear Physics, Heavy Ions, Hadrons; Theoretical, Mathematical and Computational Physics; Particle Acceleration and Detection, Beam Physics; Measurement Science and Instrumentation